2007
DOI: 10.1016/j.gloplacha.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Potential of submarine-cave sediments and oxygen isotope composition of cavernicolous micro-bivalve as a late Holocene paleoenvironmental record

Abstract: A sediment layer (43 cm thick) and surface sediments (5 cm thick) in a submarine limestone cave (31 m water depth) on the fore-reef slope of Ie Island, off Okinawa mainland, Japan, were examined by visual, mineralogical and geochemical means. Oxygen isotope analysis was performed on the cavernicolous micro-bivalve Carditella iejimensis from both cored sediments and surface sediments, and the water temperature within the cave was recorded for nearly one year. These data show that: (1) water temperature within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 56 publications
(54 reference statements)
5
38
3
1
Order By: Relevance
“…There remains an ongoing debate concerning the variability of late Holocene SST estimates for the area around the Okinawa Trough and the Ryukyu Islands. Kitamura et al (2007a) measured the oxygen isotope compositions of the micro-bivalve Carditella iejimensis obtained from surface sediments (5 cm thick) within a submarine cave named Daidokutsu (31 m water depth) at Ie Island (26°43′N, 127°50′E), Japan, located ca. 10 km west of the Okinawa Island ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There remains an ongoing debate concerning the variability of late Holocene SST estimates for the area around the Okinawa Trough and the Ryukyu Islands. Kitamura et al (2007a) measured the oxygen isotope compositions of the micro-bivalve Carditella iejimensis obtained from surface sediments (5 cm thick) within a submarine cave named Daidokutsu (31 m water depth) at Ie Island (26°43′N, 127°50′E), Japan, located ca. 10 km west of the Okinawa Island ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although the temporal resolution and duration of this proxy are not comparable to those derived from corals, it represents a thermometer at a fixed observation point that provides data in addition to coral records. Based on T δ 18 O from C. iejimensis obtained from cored sediments, Kitamura et al (2007a) identified two relatively warm intervals over the past 2000 years; at AD 340± 40 and AD 1000 ± 40, corresponding to the Roman Warm Period and the Medieval Warm Period, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of workers have recently used archival materials from submarine caves to reconstruct environmental changes during the late Quaternary (Antonioli et al, 2001;Kitamura et al, 2007, Yamamoto et al, 2008, 2009a. For example, oxygen-isotopic compositions of coralline sponges and micro-bivalves from submarine caves have been studied as proxies for palaeotemperature (Böhm et al, 2000;Haase-Schramm et al, 2003;Yamamoto et al, 2008Yamamoto et al, , 2009bYamamoto et al, , 2010Kitamura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many submarine limestone caves occur on the islands (Hayami and Kase, 1993). However, previous studies of changes in the communities of submarines caves have only considered millennial-scale variations in the species compositions of bivalves (Kitamura et al, 2007;Yamamoto et al, 2009a) and algal symbiont-bearing large benthic foraminifers (Omori et al, 2010) in Daidokutsu submarine cave (water depth, 29 m) at Ie Island, Okinawa (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%